CHARACTERISTICS OF VIRAL PROTEIN, VP-15, OF WHITESPOT SYNDROME VIRUS ISOLATED FROM INFECTED TIGER SHRIMP Penaeus monodon (Fabricius, 1798) - Andi Parenrengi; Alimuddin Alimuddin; Andi Tenriulo (Indonesian Aquaculture Journal, 2017)
White spot syndrome virus (WSSV) has caused mass mortality on tiger shrimp (Penaeus monodon) culture and adversely affects prawn industry worldwide including Indonesia. It is well known that the protein structure of WSSV plays an important role in the virus infection and morphogenesis process. A viral protein structure called VP-15 is located in the nucleocapsid of virion virus. The protein structure involves in the life cycle of WSSV in host cells. A gene encoding VP-15 could be involved in constructing the RNA interference (RNAi), so it is needed to isolate and characterize for RNAi technology purpose. The study was aimed to isolate and characterize the VP-15 from the infected WSSV tiger shrimp. The characterization of VP-15 was undertaken through assessment of nucleotide sequence, amino acid deduction, alignment nucleotide/protein searches using Genetyx and BLAST program, and dendrogram construction analysis. The results showed that VP-15 was successfully isolated in form of ORFDNA with a fragment size of 243 bp. The phylogenetic tree analysis revealed three clusters corresponding to the time (year) of isolates collection. The VP-15 consisted of 80 amino acids, two start codons (ATG), one stop codon (TAA), and one Kozak context (AAAATGG). Hydrophilic amino acid was the highest composition (44.2%), followed by neutral (31.2%) and hydrophobic (24.6%) amino acid groups. The VP-15 was rich in amino acid of lysine (21.3%), arginine (22.9%) and serine (24.6%). The successful isolation of VP-15 is a very important step in providing a basic yet suitable material in constructing the dsRNA vaccine to control shrimp diseases in aquaculture.